Refractive error and visual impairment in primary school children in Onitsha, Anambra State, Nigeria - Ngozika E. Ezinne; Khathutshelo P. Mashige (African Vision and Eye Health, 2018)
Background: Vision problems have been shown to adversely affect a child’s achievement in school.